“Bitmoji is Cool!”: Exploring the Secondary English Teachers’ Narratives Using Digital Avatar-based Pedagogical Agent - Santosa, Made Hery; Wahyuni, Safitry (Universitas Pendidikan Ganesha, 2024)
In online learning, students are likely to experience boredom, lack of motivation, reluctance, and anxiety. Bitmoji Virtual Classroom (BVC) – a virtual classroom can be one option in implementing interactive learning. This study aims to investigate the experiences of English teachers in designing interesting and interactive English learning using Bitmoji Virtual Classroom (BVC) – a virtual classroom designed as a digital avatar-based learning agent in online learning – to increase students’ interest, engagement, and motivation to learn. Using a narrative inquiry approach, this study explores the experiences of four junior high school English teachers who voluntarily participated. Data were collected through in-depth interviews and analyzed thematically. The findings show that teachers find the process of designing virtual classrooms enjoyable, aided by the attractive features of Bitmoji and Google Slides. They support the creation of effective learning and better student engagement through the help of this interactive learning media. However, they face challenges, such as the need for clearer learning guidelines during the implementation of the interactive media used. This study suggests that the use of avatar-based virtual classrooms can serve as an innovative strategy to develop creativity and increase student motivation in a virtual English learning environment.